Transition pathways towards net-zero emissions methanol production. Issue 24 (1st September 2021) - Adnan, Muflih A.; Khan, M. A.; Ajayan, Pulickel M.; Rahman, Muhammad M.; Hu, Jinguang; Kibria, Md Golam
Abstract : The race to decarbonize our energy systems has led to significant advancement in technologies for harvesting renewable energy, carbon capture and conversion. Abstract : The race to decarbonize our energy systems has led to significant advancement in technologies for harvesting renewable energy, carbon capture and conversion. Future scenarios are being envisioned where CO2 is captured from air and converted to valuable fuels and chemicals, with methanol (MeOH) being the most coveted product. Here we assess transition pathways for the sustainable production of MeOH using CO2 via direct air capture (DAC) and hybrid power via renewable photovoltaic (PV) and grid electricity. Specifically, we perform techno-economic and life-cycle analysis on technologically mature 1 st generation (water electrolysis coupled to CO2 hydrogenation) and emerging 2 nd generation air-to-MeOH (direct CO2 -to-MeOH electrolysis) routes. Our results indicate that the two transition pathways would be economically compelling only in jurisdictions where low-cost (0.02 per kWh) grid electricity is available. Furthermore, the economic feasibility of the 1 st generation route will also depend on a drastic reduction in Si-PV (300 per kW) and DAC (280 per ton-CO2 per year) capital costs. On the other hand, the 2 nd generation route will additionally need drastic performance improvement to be economically competitive, with required CO2 electrolysis current densities >300 mA cm −2, energy efficiency >50% and stack stability >2 years. The envisioned air-to-MeOH routes could lead to zero or negative CO2 emissions in jurisdictions with clean grid electricity (<50 kg-CO2 per MWh). We hope this study will garner key stakeholders to advance discussions about the cost and potential of this envisioned air-to-fuel technology.